Penerapan Green Accounting Terhadap Profitabilitas Umkm Tahu Di Surabaya - Nabila Febriyana; Refi Tri Anika; Vivi Armadhani; Maria Yovita R.Pandin (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
The purpose of this research is to find out how the profitability of UMKM Tofu producers in Surabaya is affected by green accounting. The research data was collected through interviews and surveys to research locations using a qualitative descriptive methodology. The findings show that most UMKM Tofu factories in Surabaya are aware of their lack of knowledge about green accounting and lack of environmental awareness. Due to the high cost of production, the majority of Tofu MSMEs are aware of the shortage of wastewater treatment tanks. As a result, UMKM Tahu deliberately build factories near rivers to dispose of liquid waste without being processed first.